Evaluation of plant species suitability for lowland forest landscape restoration in Lepan watersheds, Langkat District, North Sumatra, Indonesia - SAMSURI SAMSURI; ALFAN GUNAWAN AHMAD; ANITA ZAITUNAH; HALIZA KHAIRUNI TAMBUSAI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Samsuri, Ahmad AG, Zaitunah A, Tambusai HK. 2019. Evaluation of suitability of plant species for lowland forest landscape restoration in Lepan watersheds, Langkat District, North Sumatra, Indonesia. Biodiversitas 20: 2903-2909. Lepan watersheds have high management priority in North Sumatra due to healthy biophysical, socio-economic conditions and issues. Many human activities, such as conversion of forest land into settlements and oil palm plantations have resulted in decreasing the ecological functions of the forest landscape. Therefore, it is necessary to initiate efforts and actions to preserve the environment in order to prevent further damage. The effort required is to restore the already damaged ecosystem with the cultivation of species of plants in accordance with the land and soil conditions of the Lepan watersheds. Four criteria are used for determining suitable plants that can be planted as well as cultivated by the community. They are plant species found in natural forests, plant species meeting the physical and soil characteristics, plant species cultivated by community and plant species based on community perceptions. Species matching was determined by scoring and weighting method. This study found that the most suitable species for restoration activities based on these four criteria is Pterospermum subpeltatum.